IDENTIFIKASI PENGARUH PENGGUNAAN RAIL CLIMBING SYSTEM PADA PEKERJAAN KONSTRUKSI COREWALL - Redaksi Tim Jurnal (FORUM MEKANIKA, 2018)
In structural work, especially corewall, the use of conventional formwork systems decreases work effectiveness over time. PT. Total Bangun Persada, one of the stakeholders that applies innovation to increase the effectiveness of that is by using the rail climbing system as a solution to the problems faced. This study will compare the time effectiveness of conventional systems using corewall using the rail climbing system which was analyzed using cyclone to obtain effective repeat cycles. From the two systems, the results show that the corewall work using the rail climbing system is more effective with a work duration of 78 days compared to conventional system formwork with 84 days of work duration.